Exercise and disease progression in multiple sclerosis: can exercise slow down the progression of multiple sclerosis? - Ulrik Dalgas; Egon Stenager (Therapeutic Advances in Neurological Disorders, 2012)
It has been suggested that exercise (or physical activity) might have the potential to have an impact on multiple sclerosis (MS) pathology and thereby slow down the disease process in MS patients. The objective of this literature review was to identify the literature linking physical exercise (or activity) and MS disease progression. A systematic literature search was conducted in the following databases: PubMed, SweMed+, Embase, Cochrane Library, PEDro, SPORTDiscus and ISI Web of Science. Different methodological approaches to the problem have been applied including (1) longitudinal exercise studies evaluating the effects on clinical outcome measures, (2) cross-sectional studies evaluating the relationship between fitness status and MRI findings, (3) cross-sectional and longitudinal studies evaluating the relationship between exercise/physical activity and disability/relapse rate and, finally, (4) longitudinal exercise studies applying the experimental autoimmune encephalomyelitis (EAE) animal model of MS. Data from intervention studies evaluating disease progression by clinical measures (1) do not support a disease-modifying effect of exercise; however, MRI data (2), patient-reported data (3) and data from the EAE model (4) indicate a possible disease-modifying effect of exercise, but the strength of the evidence limits definite conclusions. It was concluded that some evidence supports the possibility of a disease-modifying potential of exercise (or physical activity) in MS patients, but future studies using better methodologies are needed to confirm this.